Taller De Algebra
Enviado por DianaPFC • 29 de Agosto de 2013 • 2.795 Palabras (12 Páginas) • 395 Visitas
Ejercicio No. 1
(1) x + 2y = 4 → x=4-2y
(2) 2x- 3y = 1
Solución “Sustitución”
(2) 2 (4-2y)-3y = 1 (1) x=4-2(1)
8-4y-3y = 1 x=4-2
8-7y=1 x=2
8-1= 7y
7=7y
7/7=y
y=1
Solución “Eliminación”
(1) (-2)(x+2y)=4 (-2 ) (2) 2x-3(1)=1
(1) -2x-4y= - 8 2x-3=1
(2) 2x-3y= 1 2x=1+3
- 7y= - 7 x=4/2
y=(-7)/(-7) x=2
y=1
Ejercicio No. 2
(1) x + y = -2 → x=-2-y
(2) x- y = 0
Solución “Sustitución”
(2) -2-y-y = 0 (1) x=-2-(-1)
-2-2y= 0 x=-2+1
-2y=2 x=-1
y =( 2)/(-2)
y=-1
Solución “Eliminación”
(1) x+y= -2 (1) -1+y= -2
(2) x-y= 0 y= -2+1
2x+0= -2 y= -1
x =(-2)/2
x=-1
Ejercicio No. 3
(1) x=4
(2) x+y+5=0
Solución “Sustitución”
(2) 4+y+5 =0
9+y = 0
y =-9
Solución “Eliminación”
(1) -1 (x)= -1 (4)
(1) -x = -4
(2) x+y+5= 0
y+5=-4
y= -4-5
y= -9
Ejercicio No. 4
(1) 3x+y = -1 → y = -1-3x
(2) y =3x+5 → y=3x+5
Solución “Eliminación”
(1) 3x+y= -1 (2) 2=3x+5
-3x+y=5 2-5=3x
2y=4 -3=3x
y = 4/2 (-3)/3=x
y = 2 x=-1
Solución “Método Gráfico”
x y = -1- 3x y = 3x + 5
3 -10 14
2 -7 11
1 -4 8
0 -1 5
-1 2 2
-2 5 -1
-3 8 -4
Ejercicio No. 5
(1) 2x+3y = 7
(2) 6x-2y=10
Solución “Eliminación”
(1) (-3)(2x+3y)= 7 (-3) (1) 2x+3(1)=7
(1) -6x-9y=-21 2x+3=7
(2) 6x-2y= 10 2x=7-3
-11y=-11 2x=4
y = (-11)/(-11) x= 4/2
y =1 x=2
Solución “Igualación”
2x=7-3y (2) 6x-2(1)=10
x = (7-3y)/2 6x-2=10
6x=10+2y 6x=10+2
x = (10+2y)/6 6x=12
(7-3y)/2= (10+2y)/6 x = 12/6
6(7-3y)=2(10+2y) x =2
42-18y=20-42
-22y=-22
y= (-22)/(- 22)
y =1
Ejercicio No. 6
(1) 4x-5y = -4
(2) 3x=2y-3
Solución “Igualación”
(1) 4x=-4+5y (1) x = (2 (0)-3)/3
x = (-4+5y)/4 x = (0 -3)/3
(2) 3x=2y-3 x = (-3)/3
x = (2y-3)/3 x =-1
(-4+5y)/4= (2y-3)/3
3 (-4+5y)=4 (2y-3)
-12+15y=8y-12
15y-8y=-12+12
7y=0
y=0
Solución “Determinantes”
■(x&y&r)
■(4&-5&-4@3&2&-3)
...